Health worker performance and achievement in the Inspection Visual Acetic Acid (IVA) test - Firantika Dias Puteri; Endang Budiati; Bambang Setiaji; Aila Karyus (Malahayati International Journal of Nursing and Health Science, 2025)
Background: Cervical cancer is the fourth common cancer affecting women all over the world and in the second place after breast cancer in Indonesia. There were 36,964 new cases of cervical cancer recorded in 2022 with 20,708 mortality cases per year. IVA examinations are a government program in all public health centers in Indonesia which can be done by a competent doctor and midwives. Low IVA’s screening is one of the causes of cervical cancer.Purpose: To identify the characteristic and the dominant health worker’s performance on the achievement of IVA examinations.Method: The cross-sectional analytic design study was conducted on April-July 2024. Sample was 121 doctors and midwives in 20 public health centers that were chosen by proportionate stratified random sampling. Data were collected using seven questionnaires about the supervision, compensation, infrastructure, workload, training and IVA achievements then analyzed and presented in univariate, bivariate and multivariate analysis, using chi square and binary logistic regression.Results: Supervision (p=0.000), facilities (p=0.000), compensation (p=0.000), workload (p=0.000), and training (p=0.001) are related to the achievement of IVA examinations by health workers at public health centers of Bandar Lampung City Health Department and supervision are the most dominant related factors (p=0,000 OR=11,252).Conclusion: The achievement of IVA examinations by Health workers in the Bandar Lampung City Health Service Work Area is related to supervision factors (p=0.000; OR=17.040), facilities and infrastructure (p=0.000; OR=4.499), compensation (p=0.000; OR=5.612), workload (p=0.000; OR=5.802), and training (p=0.000; OR=4.346) where good supervision can increase the performance of IVA examinations by health workers.